Social influence on Twitter: Examples & Projections - Dagla , Mavreta; Bairami , Georgia Paraskevi; Nikolaou , Freideriki; Schoinaraki , Emmanouela (Homo Virtualis, 2022)
The dominance of social media in today’s world is unquestionable. However, the target of their use has shifted over time from simple communication and information, regarding various issues, to influencing and convincing a wide range of people irrespective of their age, social and educational status. This literature review aims to present examples of social influence that have emerged in the field of public health, society and politics through twitter and to examine the ways and the extent of this influence during users’ navigation on the specific platform. The spread of the #metoo movement in Greece during the writing period, as well as the spread of conspiracy theories about covid-19 triggered the choice of this particular topic to review. Results of this literature review show that the social influence exerted via the internet, and especially via twitter, may take on much larger dimensions in space-time scale than in real conditions, due to the abundance and diversity of people to whom it is addressed. On one hand this contributes to a more widespread and faster awareness on important social issues. However, it simultaneously and inevitably leads to the uncontrolled spread of invalid information, possibly resulting in user disorientation and incorrect conclusion-making and correspondingly leading to incorrect choices in real life.